Isometric & short arc exercises effect on the quadricep muscle of patello-femoral knee pain patients. - Hasan , Sobia; Lasi , Fahad; Saleem , Saad; Fazal , Amaila; Khan , Rabia (International Journal of Endorsing Health Science Research, 2022)
Background: Anterior knee pain is the most common problem encountered by clinicians with an estimated prevalence of 15-45% around the globe. Thereby, this study aimed to determine the effects of isometrics and short arc quadriceps exercises on patients with patellofemoral knee pain. Methodology: The quasi-experimental study was conducted in Ameen Medical and Dental Centre, Karachi on a total of 80 anterior knee pain patients, including both genders and ages ranging from 16-40 years. The individuals were divided into two equal groups A and B (n=40) which followed isometric and short arc quadriceps exercises regimen, respectively. The pre and post-assessment of pain, muscle activity, muscle thickness measurement, and health-related quality of life (HRQoL) was done using Kujala assessment score, visual analog scale, Electromyography (EMG) biofeedback, and rehabilitative ultrasound imaging, respectively on the first day, 6th and 8th week of exercises session. Results: The results showed that pain was much decreased from 1st to 8th week after following Short arc quadriceps exercises (p<0.0001). The results also showed the higher muscle efficacy and HRQoL after following short arc quadriceps exercises, whereas Rehabilitative Ultrasound showed the higher effectiveness of Isometric quadricep exercises in increasing the muscle mass. Conclusion: It is concluded that the short arc quadriceps exercises have greater effectiveness in reducing pain, enhancing muscle activity, and increasing the HRQoL, whereas isometric quadricep exercises have shown beneficial effects in increasing muscle mass.